2021
DOI: 10.1094/mpmi-02-21-0043-r
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Methodologies for AssessingPseudomonas syringaepv.actinidiaeColonization and Effector-Mediated Hypersensitive Response in Kiwifruit

Abstract: The infection of Pseudomonas syringae pv. actinidiae in kiwifruit is currently assessed by numerous methodologies, each with their own limitations. Most studies are based on either a laborious method of growth quantification of the pathogen or qualitative assessments by visual scoring following stem or cutting inoculation. Additionally, when assessing for resistance against specific pathogen effectors, confounding interactions between multiple genes in the pathogen can make mapping resistance phenotypes nearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 69 publications
1
32
0
Order By: Relevance
“…Previous work showed that A . arguta plants were resistant to Psa3, associated with a quantifiable increase in ion leakage due to membrane disruption of the dying cells indicative of a hypersensitive response (HR) [ 35 ]. Leaves of A .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work showed that A . arguta plants were resistant to Psa3, associated with a quantifiable increase in ion leakage due to membrane disruption of the dying cells indicative of a hypersensitive response (HR) [ 35 ]. Leaves of A .…”
Section: Resultsmentioning
confidence: 99%
“…Using the previously described biolistic co-expression assays to measure HR-mediated reporter eclipse in AA07_03 leaves, hopZ5a was identified as the recognized effector in the hopZ5a / hopH1a effector block ( S6 Fig ). This assay, described previously, assesses whether biolistic co-delivery of an effector is able to suppress expression of a reporter GUS gene due to HR [ 35 , 42 ]. Therefore, only the single hopZ5a knockout strain was used for subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Once inside the plant cells, effector proteins can disrupt plant immune responses in a variety of ways to promote bacterial growth and infection. The presence of effector proteins can also be monitored by plant immune responses through the action of R-genes, with recognition of effector protein functions leading to an overarching immune reaction termed effector triggered immunity (ETI) (Collmer et al, 2000;Jones and Dangl, 2006;Jayaraman et al, 2021). Triggering of the ETI response can quickly shut down nascent infections in resistant plant cultivars and has thus formed the basis of future plans to engineer durable crop resistance to infection through genetic modification and selective breeding (Dong and Ronald, 2019;Laflamme et al, 2020).…”
Section: Introductionmentioning
confidence: 99%